Neferine inhibits LPS-ATP-induced endothelial cell pyroptosis via regulation of ROS/NLRP3/Caspase-1 signaling pathway - Tang, Yang-Shuo; Zhao, Yan-Hua; Zhong, Yong; Li, Xiao-Zhao; Pu, Jia-Xi; Luo, Yan-Cheng; Zhou, Qiao-Ling (Inflammation research, 2019)
Background Oxidative stress-induced endothelial dysfunction and pyroptosis play an important role during chronic kidney disease (CKD) progression. Neferine, which is an alkaloid ingredient from the lotus seed embryo, has many biological actions such as anti-inflammatory, anticancer and antioxidant. However, the role of neferine in endothelial cell pyroptosis and the involved mechanism remain obscure. The aim is to probe the protective effects of neferine on cell pyroptosis and the involved underlying mechanism. Methods After the HUVECs were primed with neferine treatment for 2 h prior to LPS and ATP exposure for 24 h, the cell proliferation was determined by BrdU; the cell LDH release was detected by LDH kits; the levels of intracellular ROS, MDA and SOD were tested by detection kits; Caspase-1 activity kit was used to determine caspase-1 activity; the contents of NLRP3, ASC, caspase-1, IL-1β, IL-18 and GSDMD were tested by RT-PCR and western blot. Results We found that neferine could inhibit LPS-ATP-induced oxidative stress and the activation of NLRP3 inflammasome signaling, and increased the endothelial cell viability and SOD production. siRNA which mediated the knockdown of NLRP3 promoted the neferine-induced inhibition effects of cell pyroptosis. Furthermore, these neferine-induced effects were reversed by the over-expression of NLRP3. Conclusions Our findings indicated neferine may reduce ROS by anti-oxidation and inhibit LPS-ATP-induced endothelial cell pyroptosis via blocking ROS/NLRP3/Caspase-1 signaling pathway, which provides the evidence for therapeutic effect in CKD.